Benzodifuran and benzodithiophene donor–acceptor polymers for bulk heterojunction solar cells1. Issue 13 (7th April 2015) - Huang, Peishen; Du, Jia; Gunathilake, Samodha S.; Rainbolt, Elizabeth A.; Murphy, John W.; Black, Kevin T.; Barrera, Diego; Hsu, Julia W. P.; Gnade, Bruce E.; Stefan, Mihaela C.; Biewer, Michael C.
<x xml:space="preserve">Abstract</x> Four new donor–acceptor copolymers were synthesized by using benzo[1, 2-b:4, 5-b′]dithiophene and benzo[1, 2-b:4, 5-b′]difuran as donors and thieno[3, 4-b]thiophene was used as the acceptor building block.